Cost-Effectiveness Analysis of Single-Tooth Rehabilitation Options - Manuel Henrique de Medeiros Neto; Rênnis Oliveira da Silva; Leopoldina de Fátima Dantas de Almeida; Edson Hilan Gomes de Lucena; Denise de Fátima Barros Cavalcante; Antonio Carlos Pereira; Yuri Wanderley Cavalcanti (Association of Support to Oral Health Research (APESB), 2024)
Objective: To evaluate the cost-effectiveness of single-tooth rehabilitation options with dental implants associated with a prosthetic crown (I+C) compared to a fixed partial denture (FPD). Material and Methods: A rapid review was carried out to identify the costs (expressed in US$) and effectiveness (expressed through success rate). Bibliographic searches retrieved 1,447 records, of which 19 studies of type randomized clinical trials were selected to collect cost and effectiveness data. Markov economic models were used to simulate hypothetical 15-year cohorts with 2000 patients using cost and effectiveness data from the rapid review under the perspective of private practice. Results: The average costs of I+C and FPD treatments were US$ 3,432.23 and US$ 3,322.52, respectively. The average effectiveness of I+C was 88.33%, with a mean follow-up time of 9.33 years, and FPD had an average yearly success rate of 82.14%, with a mean follow-up time of 11.89 years. The I+C treatment has an incremental cost-effectiveness ratio (RCEI) of US$ 170.88 compared to FPD. Conclusion: Both I+C and FPD rehabilitation options are cost-effective; I+C rehabilitation has a higher cost and greater effectiveness, being the recommended option if the patient with no contraindication.